Developing Chinese university students’ academic literacies in English language classrooms via a production-oriented approach: an action research perspective - Gao, Yajuan; Wang, Hao (Frontiers in Psychology, 2023)
Developing academic literacies is becoming an important research topic in TESOL and has received increasing scholarly attention. One of the difficulties in developing university students' academic literacies in English language speaking is the lack of authentic English language teaching and learning environment and the way to help students more effectively develop their language competence. To address this issue, this study seeks to explore academic literacies development of 24 non-English major students in an 8-week long integrated English class at a Chinese university in late 2022. Situated from a production-oriented approach (POA) action research design, this study follows the framework of typical phases of driving, enabling, and assessing activities. Quantitative data from questionnaires were analyzed via SPSS software, whereas thematic analysis and content analysis were adopted in examining the qualitative data including classroom observations, teacher reflection journals, and semi-structured interviews. Based on our data analysis, this study finds that POA can have a positive effect on improving students' participation, performance, and task completion, which improves their academic literacies. Pedagogical implications on how POA helps in facilitating EFL students' academic literacies development are discussed along with future research directions.